2002
DOI: 10.1364/josaa.19.002363
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral refractive errors in myopic, emmetropic, and hyperopic young subjects

Abstract: To gain more insight into the relationship between foveal and peripheral refractive errors in humans, spheres, cylinders, and their axes were binocularly measured across the visual field in myopic, emmetropic, and hyperopic groups of young subjects. Both automated infrared photorefraction (the "PowerRefractor"; www. plusoptix.de) and a double-pass technique were used because the PowerRefractor provided extensive data from the central 44 deg of the visual field in a very convenient and fast way. Two-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
217
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(259 citation statements)
references
References 35 publications
35
217
2
5
Order By: Relevance
“…42 The presence of local mechanisms also has important implications for optical treatment strategies for myopia. For instance, because the refractive state at the fovea is dependent on ocular changes at the posterior pole and in the periphery (ie, an expansion of the sclera in the periphery would displace the central retina in a posterior direction along the visual axis), 50 peripheral visual signals can influence central refractive development in a manner that is independent of the nature of central vision. Moreover, optical manipulations of peripheral vision, which do not alter central vision, may be effective in controlling central refractive development.…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
See 1 more Smart Citation
“…42 The presence of local mechanisms also has important implications for optical treatment strategies for myopia. For instance, because the refractive state at the fovea is dependent on ocular changes at the posterior pole and in the periphery (ie, an expansion of the sclera in the periphery would displace the central retina in a posterior direction along the visual axis), 50 peripheral visual signals can influence central refractive development in a manner that is independent of the nature of central vision. Moreover, optical manipulations of peripheral vision, which do not alter central vision, may be effective in controlling central refractive development.…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
“…By influencing the ability of the sclera to expand in a tangential manner, peripheral mechanisms acting locally could affect the axial position of the posterior retina and central refractive error. 50 For example, tangential stretching of the sclera near the eye's equator would increase central axial length without necessarily changing the shape of the posterior globe. It is also likely that the dominate role of the periphery reflects spatial summation of growth signals across the posterior globe.…”
Section: Peripheral Visual Signals Can Dominate Central Refractive Dementioning
confidence: 99%
“…[6][7][8] Even though early reports on peripheral refraction date back as early as the 1930's, 9 this subject has been more extensively studied since the 1970's. The techniques of subjective refraction and retinoscopy were approached by Rempt et al, Millodot and Lamont and Wang et al [10][11][12] Peripheral refraction was also studied by means of objective and manual optometers; 13,14 open-field autorefractors, 15,16 photorefraction, 4 double pass method, 17 and clinical aberrometers. 18 Several factors with the potential to affect peripheral refraction were also analyzed; namely age, 2,19 refractive error, 4,20 eccentric horizontal and vertical retinal locations, 21 different fixation distance 22 and the impact of anterior cornea reshaping with orthokeratology 16 or LASIK.…”
Section: Introductionmentioning
confidence: 99%
“…25 Refractive error in the peripheral retina, as compared to central refraction, shows a myopic trend in emmetropes and hyperopes. On the other hand, myopes present a peripheral refraction that is less myopic or more hyperopic than the central measurement; 4,5,26 this fact has been more intensively studied for the horizontal meridian of the eye. 21 The application of autorefractors to obtain peripheral refraction data raises the question of which is the effect of accommodation and which is the validity of such measures without cycloplegia.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Considerable human research is being carried out to study the hypothesis that defocus and astigmatism in the retinal periphery may influence the development and progression of myopia. These studies [12][13][14][15][16][17][18][19][20][21] have reported diverse peripheral refraction patterns with various levels of ametropia. However, most suggest that emmetropes and hypermetropes have relative myopic shifts in the periphery, while myopes have relative hypermetropic shifts.…”
Section: Introductionmentioning
confidence: 99%